Reading Vergil’s Aeneid: An interpretative guide, ed. Ch. Perkell, Oklahoma, 1999, 353 pp. ISBN 0-8061-3139-X (Minerva, 2019)
Review: Reading Vergil’s Aeneid: An interpretative guide, ed. Ch. Perkell, Oklahoma, 1999, 353 pp. ISBN 0-8061-3139-X